Pengukuran Pembangunan Berkelanjutan Di Indonesia - Noyo, Irfandi A.; Muliati, Muliati; Samir, Yulia Gita; Kasmawati, Kasmawati (FEB-Telkom University Publisher, 2024)
Sustainable development is an abstract idea with complex goals and different aspects. This research was conducted to determine how sustainability can be measured, especially in Indonesia. This study describes sustainability as balancing economic, social, environmental, and legal development and management. The method of analysis in this study is quantitative but within the framework of descriptive analysis. Descriptive analysis is done by looking at the data through graphs and tables. Sustainable development is assessed in two ways. The first uses partial development indicators, and the second uses a composite index. This study provides one of the empirical pieces of evidence that sustainability requires a high level of balance between dimensions (economic, social, environmental, legal, and governance). Keywords: Sustainable development; Composite index